Routledge handbook of sport governance - Shilbury, David 1958-; Ferkins, Lesley (Routledge international handbooks, 2020)
The Routledge Handbook of Sport Governance is a comprehensive and authoritative survey of the wide range of issues shaping sport governance. It considers the evolution of the sport industry from a largely amateur, volunteer-driven sector into the globalised business that it is today and examines how professionalisation has fundamentally shifted the governance landscape for sport organisations and all those working within sport. Written by a team of leading sport management scholars from around the world, the book is organised around five key themes: Part I - Overview of sport governance Part II - environmental context and policy perspectives Part III - Ownership structures and governance models: Implications for sport governance Part IV - Board roles in the governance process Part V - Future sport governance challenges Each chapter reviews the most recent research available and, in some cases, presents new data to support previously published studies. As sport governance is a relatively young field, each chapter maps future research needs to provide direction for sport governance scholars. A special feature of the handbook is a series of nine shorter research chapters in Part IV examining board roles in the governance process, tying theory to the day-to-day practical aspects of running a sport organisation. With broader and deeper coverage of the key issues in contemporary sport governance than any other book, this handbook is essential reading for students, researchers and practitioners working in sport business and management.